Caregivers of Elderly with Moderate to Total Dependence in Activities of Daily Living in Yogyakarta Indonesia: Correlation of Burden and Quality of Life - Widagdo, The Maria Meiwati; Gulo, Lise Insani; Cendrasilvinia, Herose; Manus, Widya Christine (UI Scholars Hub, 2022)
Background: Aging is accompanied by a functional decline leading to the loss of independence in conducting activities of daily living. The dependence of the elderly can cause burden that affects the quality of life of caregivers. This study aimed to assess the correlation between the burden and quality of life of caregivers looking after moderately to totally dependent elderly. Methods: This research is a cross-sectional study that used Zarit Burden Interview to assess caregiver burden and World Health Organization Quality of Life to measure the quality of life of people caring for elderly with moderate to total dependence based on the scores in Activities of Daily Living and Instrumental Activities of Daily Living questionnaires. The data were analyzed using Spearman’s rank correlation test. Results: A total of 30 caregivers participated in this study. Significant negative correlations were observed between the burden and quality of life of caregivers of elderly with moderate to total dependence in all four domains: physical (p = 0.001), psychological (p < 0.001), social relationships (p = 0.028), and environmental (p < 0.001). Conclusions: The findings imply that the burden of caring for the elderly with moderate to total dependence may affect the caregivers’ burden and quality of life in all domains.